Answer:
Below
Explanation:
The equation is x2 + bx + c
The coefficients are
● a = 1
● b
● c is the constant
The difference of the roots is | b - 2c |
Let s and p be the roots of the polynomial
● s - p = | b - 2c | (1)
● s + p = -b/a => s + p = -b (2)
(1) + (2)
● s - p + s + p = |b-2c| - b
● 2s = | b - 2c | - b
● 2s = b - 2c - b or 2s = 2c - b - b
● 2s = - 2c or 2s = 2c - 2b
● s = - c or s = c - b
We want to express b in term of c. So we will be intetsted in the 2nd equation
● s = c - b
● s - c = - b
● b = c - s